Use of allogeneic platelet-rich plasma for the treatment of autoimmune ocular surface disorders: case series - Mancini, Maura; Postorino, Elisa Imelde; Gargiulo, Ludovica; Aragona, Pasquale (Frontiers in Ophthalmology, 2023)
Purpose: To assess the effectiveness of topical allogeneic PRP eye drops for the treatment of symptoms and clinical signs in patients with severe dry eye secondary to Sjögren's syndrome (SS).Design: Case series and literature review.Methods: Six eyes from three consecutive patients with severe dry eye from SS were evaluated.They were treated with allogeneic topical PRP eyedrops: one drop 6 times daily for 3 months and post treatment follow-up evaluation 3 months after treatment suspension. We evaluated the subjective symptoms, visual acuity, tear break-up time, Schirmer's I test, fluorescein corneal and conjunctival staining, and corneal sensitivity.Results: Symptoms and visual acuity improved significantly in all patients. There was a significant improvement in corneal sensitivity and a decrease or disappearance of fluorescein corneal staining.The treatment with allogenic PRP eyedrops of patients with SS related severe dry eye, has proven to be very effective, with an improvement of symptoms and main clinical signs.